Critical issues in social studies teacher education - Adler, Susan A. (Research in social education., 2004)
Taken together, these authors explore the many and varied challenges faced by teacher educators generally, and social studies teacher educators specifically. Their analyses and recommendations provide a starting point for ongoing deliberations about the nature and challenges of the field. There are no easy answers; but continuing the discussion is crucial.